Social Dimensions of Post-Quake Programmes in Kachchh, Gujarat (India): Disaster Management Lessons - Smita Mishra Panda (International Journal of Modern Agriculture, 2020)
This article focuses on the social dimensions of post-quake rehabilitation programmes in Kachchh district of Gujarat state (earthquake of Jan 2001) in India. Several rehabilitation and reconstruction packages were undertaken by the state, NGOs, and other organizations, either independently or on a partnership basis. The focus is on rural Kachchh and the different shelter programmes. rehabilitation and resettlement programmes of a large magnitude, are bound to be ridden with problems. The issues covered are loss of village identity, caste/community politics, NGO dynamics in rehabilitation programmes, lack of gender sensitivity in the programmes and dependency syndrome with respect to the affected population. Some disaster management lessons have been derived keeping in mind the needs of the rural population, class and particularly with respect to the role of the government and the NGOs.